Family Governance and the Moral Obligation of Businesses to Serve Their Communities - R, Steffi.; Rajest, S. Suman; Regin, R.; T, Shynu (International Journal on Orange Technologies, 2023)
The concept of corporate social responsibility is increasingly being embraced by businesses of all kinds and in all areas of society. The necessity of conducting an investigation on the level of Corporate Social Responsibility performance by family businesses is one of the aims of this article. Second, the purpose of this article was to investigate how well non-family businesses perform in terms of their corporate social responsibility obligations. The practise of corporate social responsibility has continued to gain ground in the business world. In the context of a company, "Corporate Social Responsibility" refers to any extracurricular endeavours that go above and beyond the company's routine operations in order to further the common good. Corporate Social Responsibility, for example, has been shown to contribute to increased stock returns, increased access to financing, increased opportunities for companies to merge, and increased opportunities for firms to reduce the cost of their capital. These findings, which have been expressed in a variety of studies, show that companies place a great deal of importance on corporate social responsibility. For example, to demonstrate how much importance companies place on corporate social responsibility, consider the following: the findings expressed in these studies show that corporate social responsibility contributes towards increased stock returns. However, only a few studies have shown that Corporate Social Responsibility is dependent on a few determinants such as regulations, characteristics of chief executive officers, political affiliations, as well as national institutions; the study adopted questionnaire instruments to collect primary data through a survey approach from respondents from family-controlled and non-family-controlled companies. According to the data, family-controlled businesses had a poorer performance in terms of corporate social responsibility than non-family-controlled businesses.